In Silico and In Vivo Studies of β-Sitosterol Nanoparticles as a Potential Therapy for Isoprenaline-Induced Cognitive Impairment in Myocardial Infarction, Targeting Myeloperoxidase - Partha Saradhi Tallapalli; Yennam Dastagiri Reddy; Deepak A. Yaraguppi; Surya Prabha Matangi; Ranadheer Reddy Challa; Bhaskar Vallamkonda; Sheikh F. Ahmad; Haneen A. Al-Mazroua; Mithun Rudrapal; Prasanth Dintakurthi Sree Naga Bala Krishna; Praveen Kumar Pasala (MDPI AG, 2024)
Objective: This study aimed to compare the effects of β-sitosterol nanoparticles (BETNs) and β-sitosterol (BET) on cognitive impairment, oxidative stress, and inflammation in a myocardial infarction (MI) rat model using in silico and in vivo methods. Methods: β-Sitosterol (BET) and myeloperoxidase (MPO) ligand-receptor binding affinities were evaluated using Autodock Vina for docking and Gromacs for dynamics simulations. BET nanoparticles, prepared via solvent evaporation, had their size confirmed by a nanoparticle analyzer. ISO-induced cognitive impairment in rats was assessed through Morris water maze and Cook's pole climbing tests. Oxidative stress, inflammation, and cardiac injury were evaluated by measuring GSH, SOD, MDA, MPO, CkMB, LDH, lipid profiles, and ECGs. Histopathology of the CA1 hippocampus and myocardial tissue was performed using H&E staining. Results: In silico analyses revealed strong binding affinities between BET and MPO, suggesting BET's potential anti-inflammatory effect. BETN (119.6 ± 42.6 nm; PDI: 0.809) significantly improved MI-induced cognitive dysfunction in rats (p < 0.001 ***), increased hippocampal GSH (p < 0.01 **) and SOD (p < 0.01 **) levels, and decreased hippocampal MDA (p < 0.05 *) and MPO levels (p < 0.01 **). BETNs also elevated cardiac GSH (p < 0.01 **) and SOD (p < 0.01 **) levels and reduced cardiac MPO (p < 0.01 **), CkMB (p < 0.001 **) and LDH (p < 0.001 **) levels. It restored lipid profiles, normalized ECG patterns, and improved histology in the hippocampal CA1 region and myocardium. Conclusions: Compared with BET treatment, BETNs were more effective in improving cognitive impairment, oxidative damage, and inflammation in MI rats, suggesting its potential in treating cognitive dysfunction and associated pathological changes in MI.